Elaboration of plasma-dielectric wakefield accelerator - Onishchenko, I.N.; Berezina, G.P.; Galaydych, K.V.; Kniazev, R.R.; Linnik, A.F.; Markov, P.I.; Omelaenko, O.L.; Pristupa, V.I.; Sotnikov, G.V.; Us, V.S. (Вопросы атомной науки и техники, 2016)
Theoretical and experimental investigations of the physical principles of wakefield accelerator based on the excitation of accelerating wakefield in the plasma-dielectric structure by a long sequence of relativistic electron bunches are presented. Enhancing the wakefield intensity is supposed to be achieved by using multibunch regime of excitation for the coherent summation of wakefields of individual bunches and resonator regime for wakefields accumulation. The acceleration of bunches in the total (plasma+dielectric) wakefields is realized by detuning of bunch repetition frequency relatively to the frequency of the excited wakefield. In such a way the sequence of bunches is divided into exciting and accelerated parts due to displacing latter part of bunches into accelerating phases of wakefield excited by a former part of bunches of the same sequence. The influence of plasma in the transit channel on the amplitude of excited plasma and dielectric wakefields and focusing exciting and accelerated bunches is investigated.